DIGITAL PRIVACY PROTECTION: APPLYING STEGANOGRAPHY IN TEXT MESSAGES - Fadhlirrahman Baso (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
Digital privacy protection has become a crucial priority in today's digital age, given the increasing risks of personal data leaks. Steganography, as a technique of concealing messages within other media, emerges as an innovative solution to safeguard text messages from unauthorized access. This article examines the implementation of steganography, specifically the Least Significant Bit (LSB) method, in protecting user's personal data. Through experiments conducted on the pelock.com website, this method successfully embedded text messages into images without compromising visual transparency. This success demonstrates the potential of steganography, especially LSB, as an effective tool in securing confidential information. Detailed implementation steps and test results indicate that steganography can serve as an additional layer in maintaining data confidentiality in the complex and evolving digital environment. The research also identifies potential avenues for further development, including the integration of artificial intelligence to enhance overall data security.